Restoration of the Severely Compromised Maxilla Using the Multi-Cup Denture - Robert L. Engelmeier, DMD, MS,1 Maria L. Gonzalez, DDS, MS,2 & Maribel Harb, DDS, MS3 (Journal of Prosthodontics, 2008)
Among the millions of edentulous Americans, a persistent minority have not been able tolerate wearing dentures